Bioeconomy and Social Innovation: Challenges in Industry 4.0 - Velásquez, Melbin (2023)
Knowledge management, and the growth of the articulation between different science disciplines in industry 4.0 have favored the creation and implementation of technologies and has given rise to the development of the bioeconomy. With the purpose of identifying in the academic literature the articulations and challenges posed on the bioeconomy and social innovation in the scenario of the fourth industrial revolution, the present study was carried out from a qualitative approach, for which a descriptive-exploratory study was designed to review articles that considered the academic literature of Latin America and the Caribbean from the year 2010. The Web Scopus, Scielo, Sciencie Direct, Dialnet and Google Scholar databases were consulted. The academic literature found was scarce, with 21 relevant documents for this study; and, although the articulation of the bioeconomy and social innovation in industry 4.0 is incipient in them, the concepts of bioeconomy and social innovation, the categories emergent and the challenges that are suggested in this scenario of knowledge are recognized.